T-Type-Based Dual-Active-Bridge DC-DC Converter With Voltage Balancing Capability for Bipolar DC Distribution System - Jun Young Lee; Jun-Suk Lee; Jee-Hoon Jung (IEEE Access, 2025)
A dual-active-bridge (DAB) converter has been widely used to construct the dc bus voltage of a dc distribution system. However, in the case of a bipolar dc system, conventional DAB converters fail to regulate the bipolar dc bus voltage levels due to the absence of voltage balancing capability. Existing solutions, such as voltage balancers, require additional circuits and bulky balancing inductors, significantly reducing power density and increasing the system’s complexity. To solve this issue, this paper proposes a T-type-based DAB converter that can obtain voltage balancing capability without additional voltage balancing circuits and bulky inductors. An enhanced switching modulation is proposed for the T-type bridge to individually regulate the bipolar output power flows for the voltage balancing capability. Finally, a 2-kW prototype is developed to verify the performance of the proposed converter.